A design model for fibre reinforced concrete bending elements with longitudinal pre-stressed steel and FRP bars - Taheri, Mahsa (2012)
A close form solution to calculate the moment-curvature and load-deflection response of strain-softening and strain-hardening fibre reinforced concrete (FRC) elements failing in bending and reinforced longitudinally with pre-stressed steel and fibre reinforce polymer (FRP) bars is presented. This hybrid reinforcement is used for the development of high durable pre-fabricated and cost competitive beams. Pre-stressed FRP bars are applied with the minimum concrete cover, in order to take into account the benefits derived from the relatively high tensile strength of these bars and their immunity to corrosion. Pre-stressed steel bars, with a larger concrete cover have the purpose of providing the necessary ductility and assure the resistance of the beam in case of a fire occurrence. To replace completely the steel stirrups, a high performance fibre reinforced concrete is used. The predictive performance of the model is assessed by taking advantage of FEMIX, a FEM-based computer program. The model is finally utilized in a parametric study in order to evaluate the impact of post-cracking performance of FRC and applied pre-stress percentage on structural performance of FRC beams.